RELATIONSHIP BUTTERFLY OF DIVERSITY (ORDO LEPIDOPTERA) WITH TROPICAL PLANTS IN THE MURIA MOUNTAIN KUDUS, CENTRAL JAVA - Melisa Oktaviani Sukma; Lianah Lianah; Saifullah Hidayat (Jurnal Biodjati, 2021)
Indonesia is a megadiverse country. Butterflies become one of the Indonesian diversities. Indonesia has the second-highest butterfly species in the world with more than 2000 species. Flower plants are used by butterflies as hostplants and foodplant. The aims of this research were to know butterflies’ diversity and food plants in Mount Muria at Kudus City,  Central Java. The research used the quadran sampling transect method with three stations (along 2 km). The research was conducted in March and June 2020. The tools used were insect net, termohigrometer, lux meter, digital camera, roll meter, GPS, ja,r and identification book. Data on butterflies diversity were analyzed by Shannon-Wiener (H’), Evenness index (E), Relative Abundance (Pi), Simpson Dominance Index (D), Density (KR) Frequency (FR), and Important Value Index (IVI).  Results of the research showed that at least 40 species of six family butterflies found at Mt. Muria. Butterflies at Mt. Muria area has a medium diversity, medium evenness, and low dominance. Leptosia nina has the highest relative abundance, frequency, density and IVI (Important Value Index). Butterflies were found frequently feeding on flowers as hostplants and foodplants. 31 species of flower plants were found at Mt. Muria. The most used plant as hostplants and foodplants by butterfly is Lantana camara, and Chromolaena odorata from Verbenaceae and Asteraceae.